The Differences of Depression Level and Risk of Suicide in Medical Students in Surabaya - Amalia, Agnes; Sulistiawati; Azimatul Karimah (Jurnal Psikiatri Surabaya, 2022)
Background: Medical students are at risk of depression because of the enormous demands and pressures on their learning systems.Research has documented that the majority of young suicide victims die during depression. Objective: 1. To Analyze the difference in the level of depression and risk of suicide in Faculty of Medicine, Airlangga University students based on year of class. 2. To Measure the prevalence of depression and suicide risk in Faculty of Medicine, Airlangga University  students based on year of class. Methods: This study used an observational analytic cross-sectional study design with consecutive sampling technique. The population and sample were undergraduate medical students of 2019, 2018, and 2017 Airlangga University, Surabaya. Depression level was measured using PHQ-9 and suicide risk was measured using BSSI. Results: Faculty of Medicine, Airlangga University students class 2019 had the highest average depression score compared to class 2018 and 2017, The suicide risk rate of subject in class of 2019 is 1 person (1.0%), in 2018 there is 1 person (1.0%) and in 2017 there are 3 people (3.0%). Conclusion: There is no significant difference in the level of depression. The incidence of medical faculty students at risk of suicide totally 5 person. Therefore the low risk of suicidality among these students is good news. Faculty of Medicine, Airlangga University must maintain the management of education and always pay attention to mental health factors in students. However, cases of depression in students need special attention from the university.